Biological and Chemical Content in Nature and Society Education: From the Perspective of Teachers in Serbia - Nikolić, Ivko A.; Župić, Ajdina A.; Milosavljević, Predrag D. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
The subject of research in this paper relates to the representation of biological and chemical content in the existing curricula of the subjects World Around Us and Nature and Society, as well as the way in which these content are implemented in teaching. The research included 534 teachers from different schools across the territory of the Republic of Serbia. Descriptive methods and surveys were used during the research, while the data were analysed both quantitatively and qualitatively. The results indicated a sufficient representation of biological and chemical content in the curricula of the World Around Us and Nature and Society subjects, with clearly defined and specific learning outcomes. A large number of teachers believe that the biological and chemical content in the curricula is appropriate for children’s capabilities, and that teaching aids and digital technologies are used satisfactorily during content delivery. The most suitable methods and settings for teaching natural and social content, according to teachers, are laboratory-experimental methods and out-of-class teaching, which also represent the highest quality ways of acquiring knowledge empirically.
Keywords: biological and chemical content; nature and society; teachers; teaching